A Study on Coverage Evaluation, Compliance and Awareness of Mass Drug Administration for Elimination of Lymphatic Filariasis in Osmanabad District - Godale , Lata B; Ukarande , Balaji V (National Journal of Community Medicine, 2012)
Problem statement: Mass drug administration is carried out since 2004 in endemic area of India but mass drug administration as a preventive measure will be effective only when the compliance of drug is satisfactory and this is possible only when enough motivation of drug distributors and consumer is there. Lymphatic filariasis though non fatal is responsible for considerable suffering, deformity, disability and it is fourth common cause of disability worldwide. So the present study was carried out to evaluate, coverage, compliance and reasons for non compliance and awareness of Lymphatic Filariasis. Method: Present study is cross-sectional, observational study done by cluster sampling method. There are four clusters, 3 rural and 1 urban that were selected randomly. 120 houses were visited. Result: Coverage reported by District Malaria Office Osmanabad was 89.37%, little higher, in rural area (89.83%), than urban area (87.36%). The evaluation survey carried by P.S.M. team and they found the compliance of drugs by eligible population, was 73.1% which is less than required compliance i.e. 85%. It was higher in rural area (75.58%) than urban area (64.75%) the difference was statistically significant (z=1.957, p<0.05). The most common cause of non compliance was fear of side reactions of drugs (45.38%), followed by unawareness of L.F. 60% of eligible population did not know the purpose of administration drugs, cause, route of transmission, symptoms and signs of Lymphatic Filariasis so the reluctance was there for consumption of drugs. Conclusion: So to improve compliance there is need to strengthen awareness programme by health staff together